DESIGN OF â€œPUTRI KUMALAâ€ POP-UP BOOK AS CHILDREN STORYTELLING - Rizka, Maulia (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Storytelling is a positive activity that can help stimulate various aspects of child development. Storytelling activities were usually done by parents or storytellers for their children. Folklore is one of many stories on the topic of storytelling. But with the development of folklore as a topic in storytelling increasingly displaced by the influx of foreign culture. Princess Kumala is one of the folk stories from the Semarang Regency that has an interesting storyline and contains moral values that can be exemplary. In this study project, the author wanted to visualize the folklore of Princess Kumala into a pop-up book as a media in storytelling. Pop-up books can offer a new experience of reading stories more interestingly and interactively. With the creation of pop-up book, Princess Kumala is expected to be an interactive media for parents or storytellers in delivering a story. As well as a means of preservation of local folklore